Pengaruh Harga Pokok Penjualan dan Biaya Operasional terhadap Laba Bersih Pada PT Indocement Tunggal Prakarsa Tbk: The Effect of Cost of Goods Sold and Operating Costs on Net Profit at PT Indocement Tunggal Prakarsa Tbk - Ardianti Sulistia; Aulia Syafittri; Qurratu'ain Salsabila; Maria Alfiani Pare; Mutiara Tahyanda Putri (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
The increasingly intense competition in the cement industry requires companies to manage expenditures effectively and efficiently in order to maintain profitability. Cost of Goods Sold and Operating Expenses are two major cost components that affect a company’s net profit; therefore, their management requires careful attention. The purpose of this study is to analyze the effect of Cost of Goods Sold and Operating Expenses on Net Profit at PT Indocement Tunggal Prakarsa Tbk. The method used in this research is quantitative with a causal associative approach. The data analyzed were obtained from the quarterly financial statements of PT Indocement Tunggal Prakarsa Tbk for the period 2016–2025, sourced from the company’s financial documents. The analytical technique used was multiple linear regression supported by the IBM SPSS Statistics application. The results of the study indicate that Cost of Goods Sold has a significant effect on Net Profit with a significance value of 0.018. Meanwhile, Operating Expenses have a significance value of 0.687 > 0.05, which means that they do not have a significant effect on the company’s Net Profit. Both independent variables simultaneously contribute to Net Profit. Simultaneously, the model obtained an F-value of 14.071 with a significance value of 0.000; therefore, H₀ is rejected and Hₐ is accepted, indicating that both variables have a significant effect. The R Square value of 0.432 indicates that the Cost of Goods Sold and Operating Expenses variables are able to explain 43.2% of the variation in Net Profit, while the remaining 56.8% is explained by other variables outside the research model. The conclusion of this study emphasizes that effective cost control is crucial in increasing the company’s net profit. Therefore, companies need to implement optimal cost control to improve financial performance and competitiveness.